Drought survival strategies, dispersal potential and persistence of invertebrate species in an intermittent stream landscape. (2nd July 2015) - Chester, Edwin T.; Miller, Adam D.; Valenzuela, Isabel; Wickson, Steve J.; Robson, Belinda J.
Summary Intermittent stream systems create a mosaic of aquatic habitat that changes through time, potentially challenging freshwater invertebrate dispersal. Invertebrates inhabiting these mosaics may show stronger dispersal capacity than those in perennial stream systems. To relate different combinations of dispersal and drought survival strategies to species persistence, we compared the distribution and dispersal potential of six invertebrate species across all streams in a montane landscape where drying is becoming increasingly frequent and prolonged. Invertebrates were collected from seventeen streams in the Victoria Range, Grampians National Park, Victoria, Australia. The species analysed were as follows: the caddisflies Lectrides varians Moseley (Leptoceridae) and Agapetus sp. (Glossosomatidae); the mayflies Nousia AV1 and Koorrnonga AV3 (Leptophlebiidae); the water penny beetle Sclerocyphon sp. (Psephenidae); and a freshwater crayfish Geocharax sp. nov. 1 (Parastacidae). These species were widespread in the streams and varied in their dispersal and drought survival strategies. The distribution of each species across the Victoria Range, their drought responses and within‐stream habitat associations were determined. Hypotheses of the dispersal capacity and population structure for each species were developed and compared to four models of gene flow: Death Valley Model (DVM), Stream Hierarchy Model (SHM), Headwater Model (HM) or panmixia (PAN). Molecular genetic methods were then used to infer population structure and dispersal capacity for each species. The large caddisfly Lectrides resisted drought through aestivation and was panmictic (PAN) indicating strong dispersal capacity. Conversely, the small caddisfly Agapetus relied on perennially flowing reaches and gene flow was limited to short distances among stream headwaters, resembling the HM. Both mayflies depended on perennial surface water during drying and showed evidence of gene flow among streams: Koorrnonga mainly dispersed along stream channels within catchments, resembling the SHM, whereas Nousia appeared to disperse across land by adult flight. Sclerocyphon relied on perennial water to survive drying and showed an unusual pattern of genetic structure that indicated limited dispersal but did not resemble any of the models. Geocharax survived drought through aestivation or residence in perennial pools, and high levels of genetic structure indicated limited dispersal among streams, resembling the DVM. Despite good knowledge of species' drought survival strategies, the population structure of four species differed from predictions. Dispersal capacity varied strongly among species; most species were poor dispersers and only one species showed panmixia. Therefore, intermittent stream species may not necessarily be better dispersers than those in perennial streams. Species showing strong drought resistance strategies differed in dispersal capacity. Knowledge of life‐history characteristics, distribution and refuge use does not necessarily enable successful prediction of invertebrate dispersal pathways or population structure. Dispersal among intermittent streams may be restricted to relatively short distances (km) for most invertebrate species. Thus, frequent drought refuges (perennial water) that provide strong connectivity to subpopulations through stream flow (hydrological dispersal), or continuous terrestrial vegetation (flight dispersal), will be critical to maintain genetic diversity, adaptability and population persistence.